What Does ASEAN Mean to ASEAN Peoples? (The Philippine Case) - Sheila V. Siar; Jose Ramon G. Albert; Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2017)
Using a purposive online and paper-based survey and focus group discussions with select target groups, this study makes inferences about the level of awareness of the Filipino people on ASEAN; their perceived problems confronting the Philippines and ASEAN; and their aspirations, concerns, and hopes for the association. It reveals moderate familiarity about ASEAN, as well as modest identification as ASEAN citizens, which improves with age and experience. There is also a general sentiment that Philippine membership in the association is beneficial for the country, albeit only moderate as well. Media coverage on ASEAN is also perceived to be inadequate. The study validates the most immediate concerns being faced by the Philippines today, notably affordable internet connection, poverty, corruption, agriculture and food security, and energy provision and price. Most pressing regional-level concerns are climate change and natural disasters, territorial/maritime disputes, trade and investment issues, agriculture and food security, and income disparity and social inequality. These reflect the priorities that ASEAN leaders should focus on in the immediate future to remain relevant and responsive to the needs of ASEAN peoples. Aspirations are high for ASEAN to realize its integration agenda and to play an active role in global negotiations and forums and for its member-states to achieve inclusive economic prosperity. How to realize these aspirations rests in part on the ability of its member-states to work harmoniously with one another and contribute actively toward the realization of the ASEAN Community Vision. For its part, ASEAN has to provide a strong leadership role in integrating its member-states, which individually are also confronted by a host of problems. As ASEAN's coordinating body, its Secretariat needs to strengthen its capability so it can provide more effective technical support to the association in meeting its goals and aspirations.
Keywords: 330; Philippines; food security; regional integration; ASEAN; climate change; agriculture; ASEAN Secretariat; Association of Southeast Asian Nations; internet connection; poverty; corruption; international relations